2018
DOI: 10.1002/anie.201800906
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing and Organizing Bi3Cu4 and Bi7Cu12 Nanoclusters in Two‐Dimensional Metal–Organic Networks

Abstract: Multinuclear heterometallic nanoclusters with controllable stoichiometry and structure are anticipated to possess promising catalytic, magnetic, and optical properties. Heterometallic nanoclusters with precise stoichiometry of Bi Cu and Bi Cu can be stabilized in the scaffold of two-dimensional metal-organic networks on a Cu(111) surface through on-surface metallosupramolecular self-assembly processes. The atomic structures of the nanoclusters were resolved using scanning tunneling microscopy and density funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…5a bottom). The similar situation that only the metal atoms with a bigger size in the heterometallic clusters are discernable by STM was also reported by Yan et al recently 30 .…”
Section: Structures Of the Coordinated Multi-ce-containing Clusterssupporting
confidence: 86%
See 2 more Smart Citations
“…5a bottom). The similar situation that only the metal atoms with a bigger size in the heterometallic clusters are discernable by STM was also reported by Yan et al recently 30 .…”
Section: Structures Of the Coordinated Multi-ce-containing Clusterssupporting
confidence: 86%
“…3b. The similar phenomenon was also found by Yan et al 30 showing that the evaporated metal atoms were bridged by the intrinsic adatoms to form coordinated heterometallic clusters on surfaces. The Ce-Ce distance in the optimized model of the Ce 2 Au 2 (CN) 6 motif (4.95 Å) is consistent with the experimental value (4.7 ± 0.4 Å) by taking the measurement error into account.…”
Section: Structures Of the Coordinated Multi-ce-containing Clusterssupporting
confidence: 83%
See 1 more Smart Citation
“…In fact, there are several recent predictions based on ab initio modelling suggesting that honeycomb and kagome metal‐organic networks could host exotic quantum phases, for example, topological insulators . However, most of the metal‐organic networks that have been obtained are using 3d transition metals, with only a few reports on heavy metals which can provide strong spin‐orbit coupling …”
Section: Figurementioning
confidence: 99%
“…Thus, on-surface Ullmann-like coupling reaction based on non-metallic surfaces requires further dedicated explorations for the fabrication of tailored nanoarchitectures, and the substrate catalytic activity also needs to be properly considered. Bismuth, known as a typical semimetal with the reduced surface activity, was introduced recently in the form of Bi-metal complex into both the molecular self-assembly and on-surface reaction [31][32][33] , whereas the catalytic performance of bismuth was still under debate, to some extent. For instance, it was demonstrated that the DBBA precursor got completely desorbed on the bismuth decorated Au(111) surface and therefore no Ullmann-like coupling was observed 31 .…”
mentioning
confidence: 99%